2004
DOI: 10.1111/j.1742-7924.2004.00007.x
|View full text |Cite
|
Sign up to set email alerts
|

Keeping a good heart: The experience of Japanese elders in a health‐care facility for the elderly

Abstract: Aim: To clarify the experience of elderly people admitted to a health-care facility for the elderly. Methods: An ethnographic approach and qualitative descriptive design was used to understand and describe the viewpoints of the elderly living in a health-care facility. A semistructured interview was conducted in the resident's room. One at a time, the transcript of each participant's interview was read repeatedly and the parts corresponding to the participant's experience were extracted and analysed qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In the past decade, some research has tried to develop effective practical nursing strategies through the qualitative study of interview data (Ellis & Rawson, 2015;Hamahata et al, 2004;Kobayashi et al, 2008;Lillekroken, Hauge, & Slettebø, 2015;Liu, 2013;Oosterveld-Vlug et al, 2014). However, the results from those studies do not go much beyond a conventional framework and are difficult to apply in the field due to several critical reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, some research has tried to develop effective practical nursing strategies through the qualitative study of interview data (Ellis & Rawson, 2015;Hamahata et al, 2004;Kobayashi et al, 2008;Lillekroken, Hauge, & Slettebø, 2015;Liu, 2013;Oosterveld-Vlug et al, 2014). However, the results from those studies do not go much beyond a conventional framework and are difficult to apply in the field due to several critical reasons.…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, the development of specialized and practical nursing strategies, which are distinguished from conventional frameworks that focus on rehabilitative purposes, is highly desired to efficiently serve this type of complex-disability group (Carpenter, Hastie, Morris, Fries, & Ankri, 2006;Ericsson, Malmberg, Langworth, Haglund, & Almborg, 2011). Although the majority of this disability group (>40%) resides in nursing homes (National Health Insurance System, 2016) and constitutes a clear need for customized nursing guidelines and standards based on empirical knowledge, qualitative case studies to develop efficient nursing interventions that target this group have not been explored to date (Hamahata, Magilvy, Hoshino, & Komatsu, 2004;Kim, Choi, Kim, Kim, & Chang, 2016;Kobayashi, Yamamoto-Mitani, Nagata, & Murashima, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several research efforts have included cultural aspects with respect to resilience studies (Hamahata et al. 2004; Hunter 2001; Tummala‐Narra 2007; Ungar 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies on persons entering HCFEs have focused on their adaptation to the new lifestyle (Yuasa et al ., 1996), have examined self‐determination in the decision to enter a facility (Sase, 1997), and have clarified people’s experience during the time of residence (Hamahata, Magilvy, Hoshion & Komatsu, 2004). However, there have been no studies in which the lifestyle of older persons was continuously observed in the immediate period after they entered a facility to elucidate the ways such older people cope with changes in their living environment.…”
Section: Introductionmentioning
confidence: 99%